Effect of Time and Burial Depth on Breaking Seed dormancy and Germination of Weed Seeds - marzie mazhari; M.R. Tadayon (Majallah-i ḥifāẓat-i giyāhān, 2016)
Introduction: Weeds limit crop growth, development and yield through competing. Seed bank of weeds in field is one of the sources which can affect weed management and their control methods. Environmental conditions during seed maturation and following dispersal interact to influence the germination phenology of many species. Disturbance plays a key role in the maintenance of habitat for many plant species, particularly referrals, for example, fire ephemerals, desert annuals, and arable weeds. Seed germination and emergence depend on endogenous and exogenous factors. Viable seeds are dormant when all environmental conditions are appropriate for germination but seeds fail to germinate. Thus, dormancy plays an important ecological role in preventing seed germination, being a major contributor to seed persistence of some species in soil. Buried seeds of annual weeds are certainly subjected to different soil moisture conditions during their dormancy release season (winter) according to the annual rainfall pattern and burial depth. Shallow buried seeds are exposed to soil moisture fluctuations that could affect their dormancy status. Laboratory studies showed that desiccation and subsequent re-hydration of seeds could stimulate germination and modify seed light requirements. Seeds buried in deeper layers of the soil would not be exposed to such fluctuations in soil moisture, but would be exposed to different soil moisture environments depending on weather and soil characteristics. The effects of interactions between temperature, and soil or seed moisture, on seed dormancy changes have been reported for several species. Therefore, the objectives of this study were to determine the effect of time and burial depth treatments on seed germination and seedling emergence of Aegilops cylindrica, Agropyrom repens, Avena fatua, Bromus dantoniae, Cynodon dactylon, Cyprus rotundus, Setaria viridis, Anthriscus sylvestris, Centurea cyanus. Materials and Methods: In order to evaluate the effects of time and burial depth on breaking seed dormancy and percentage of germination of 27 dominants weed in Shahrekord region, an experiment was conducted at the research field at Shahrekord University in 2013. The experimental design set as factorial based on completely randomized design with three replications. Treatments consisted of three burial time levels (1, 2 and 3 months) and 4 burial depth (0, 5, 15 and 25 cm from surface soil layer) after 1, 2 and 3 months of burial. Results and Discussion: Results showed that the time and the depth of burial treatments had significant effect on breaking seed dormancy and germination percentage. Seeds retrieved from the soil surface showed highest dormancy percentage and breaking dormancy with increasing the depth and time of seed burial. The results showed that the effects of three burial times, burial depth and interaction of burial time and burial depth had significant effects on dormancy breaking and germination of weed seeds. The bitter herbs of expression and parsnip, the highest percentage of seed dormancy breaking. Germination of Geobelia alopecuoides and Anthriscus sylvestris was observed from seed burial depth of 15 cm. However, the germination percentage, between two and three seed burial months, did not show any significant difference. In this study, Convolvulus arvensies, Rumex acetisella and, Avena fatua in the highest depth (25 cm) had the maximum seed germination. Tillage would bury weed seeds and may help to preserve some seeds, because the seeds on the soil surface or near it, are prone to hunting or decay that eventually, their number is reduced in the soil seed bank. Weed seeds of Centurea cyanus, Geobelia alopecuoides, Turgeniala tifolia, Tragopogon collinus, Bromus dantoniae and Anthriscus sylvestris had more germination percentage with increasing depth to 15 cm, but beyond this depth due to the negative impacts of increased depth, seed germination declined sharply. In fact, the results of this study showed that, based on vertical distribution of seeds, at depth of more than 15 cm, weeds seed germination would be prevented. Seeds for germination, requires special conditions of temperature and moisture, and for this seeds, probably favorable conditions for germination were obtained between soil surface and 15 cm of burial depth. Overall, after two months of burial depth of 15 cm, weed seed showed highest breaking dormancy and germination percentage.